Teaching nutrition and sustainable food systems: justification and an applied approach - Campbell, Christina Gayer; Feldpausch, Gretchen (Frontiers in Nutrition, 2023)
Systems thinking is an essential skill for solving real-world problems, supporting lasting, impactful change, and creating desired futures. Transdisciplinary teaching and learning should be integrated into higher education to ensure students have the knowledge and skills to prosper in an ever-changing world. Education that addresses the interconnectedness of food systems is fundamental in cultivating future generations equipped to mitigate complex problems, such as hunger, nutrition-related chronic disease, and the climate crisis. Connecting the food, agriculture, and nutrition sectors is vitally important for improving human and planetary health and well-being. While we continue to acknowledge that it is critically important to teach systems thinking in the context of sustainable food systems limited resources are available to facilitate this type of learning. Historically, a “triple-bottom-line” approach focusing on economic, environmental, and social perspectives has been used to define sustainability. In contrast, including nutrition and health may provide a more robust view and even greater consideration for the system in its entirety. The sustainable, resilient, healthy food and water system framework, addressing all four pillars, can be used in higher education to help evaluate the sustainability of food and compare methods of production, place, and dietary patterns. This paper justifies the need for addressing sustainability issues in the context of nutrition and provides an educational approach to support student understanding and application of a systems thinking approach.